Woolf, R., Cicero. The Philosophy of a Roman Sceptic, Londres-Nueva York, Routledge, 2015, 260 + vii pp, ISBN: 978-1-84465-840-4 - María Emilia Cairo (Auster, 2017)
Reseña: Woolf, R., Cicero. The Philosophy of a Roman Sceptic, Londres-Nueva York, Routledge, 2015, 260 + vii pp, ISBN: 978-1-84465-840-4